Adsorption Analysis of Mn(VII) from Aqueous Medium by Natural Polymer Chitin and Chitosan - Gupta, Vikal; Agarwal, Jaya; Sharma, Manisha; Solanki, Parag (Asian Journal of Chemistry, 2010)
Batch experiments were carried out for the adsorption of Mn7+ ions on to natural polymer chitin and chitosan. Several variables viz., initial adsorbent concen-tration, pH, temperature and contact time were also evaluated. Equilibrium data were fitted to the Langmuir and Freundlich isotherm equation.